A Comparative In-vitro Study of the Viability of Cultured Primary Normal Human Epidermal Keratinocytes on Cellular and Acellular Human Amniotic Membrane - Mohd Yusri, Ahmad Fozi (Universiti Sains Malaysia, 2009)
Skin is the largest organ in human body. It plays important role to regulated and maintain human body homeostasis. Based on this condition, burned skin needs rehabilitation in order to reduce and avoid disturbances of body homeostasis. This study aimed to assess the ability of Human Amniotic Membrane (HAM) as scaffold for the growth of keratinocytes in-vitro. The HAM's epithelium had been removed using enzymatic technique namely dispase and trypsin-EDTA. De-epithialized HAM (also known as an acellular of HAM) was used as the main scaffold for the cultured primary normal human epidermal keratinocytes (pNHEK). Cell viability was compared between deepithialized HAM and HAM without de-epithialization (also known as cellular HAM) for the three consequence days. Epithelium of HAM was successfully removed via dispase and trypsin-EDT A, as confirmed by histochemical and cytochemical analysis. De-epitheliazed HAM sustained better cell viability only at the first 24 hours compared with the HAM without de-epithialization. However, viable cells were deserved only at 48 hours postseeding of pNHEK on the HAM without de-epithialization. In conclusion, HAM can be deepithialized using enzymatic technique. De-epithialized HAM and HAM without deepithialization can sustain the growth of pNHEK. Result of this study will use to produces specific kind of HAM for healing of skin burn.